Exploration of patient and caregiver cancer education using electronic health records. Issue 1 (January 2022) - Hekman, Daniel J.; Rodakowski, Juleen; Brick, Rachelle S.; Cadmus-Bertram, Lisa; Fields, Beth
Abstract: The objective of this short report was to describe types of education provided to older, hospitalized patients with cancer and their caregivers using electronic health record data. A total of 437 patients, representing 512 inpatient stays (admissions), met the inclusion criteria. The sample were predominately male (58%) and White (95%). The average patient age at first admission was 74 years (SD 6.21 years) and the average length of admission was 5 days (SD 3.41 days). Out of all admissions, 89% included at least one documented education session with a provider. Three important results emerged from this study 1) education on medications is commonly conveyed to cancer patients (77%), 2) nurses are primarily responsible for providing education (65%), and 3) caregivers are infrequently involved (41%) in patient education. Additional educational topics tailored to the long-term needs of older adults with cancer are warranted. These topics should be delivered by an array of interprofessional care providers with demonstrated competency. Lastly, patient education should ensure inclusion of caregivers as part of the interprofessional cancer care team to promote successful management of cancer-related concerns.